Managerial skills, technology adaptation and firm performance: Mediating role of process innovation and product innovation - Nabila Asghar; Amira Khattak; Muhammad Hassan Danish; Ijaz Hussain Bokhari; Muhammad Waris (Cogent Business & Management, 2023)
The main aim of every organization is to improve performance and productivity, but this is only possible with efficient management techniques and technology that produces results. Thus, the main aim of this study is to analyze the effect of managerial skills and technology adaptation on firm performance and productivity through the mediation channel of process innovation and product innovation using the PLS-SEM technique. The data for this study is collected from 150 managers of manufacturing industrial firms located in Lahore, the second largest city in Pakistan. The present used the purposive sampling technique to achieve the research objectives. The study's empirical findings reveal that managerial skills and technology adaptation are positively and significantly related to process and product innovation. Indirect and total effects show that managers' skills, technology adaptation, process innovation, and product innovation are positively and significantly related to the productivity and performance of firms. The present research is focused on the implementation of new technology and innovation.
Keywords: J24; L25; O31; Q55; 650; managerial skills; performance; process innovation; product innovation; productivity; technology adaptation